Chemoradiation comparing cisplatin versus carboplatin in locally advanced nasopharyngeal cancer: Randomised, non-inferiority, open trial - Imjai Chitapanarux (2018)
Purpose: This single centre, open labelled, randomised non-inferiority trial compared concurrent chemoradiotherapy with carboplatin versus standard concurrent chemoradiotherapy with cisplatin in patients with locoregionally advanced nasopharyngeal cancer (NPC). Patients and methods: From August 1999 to December 2004, 206 patients with locally advanced NPC were randomised with 101 to cisplatin arm and 105 to carboplatin arm. Planned radiotherapy was the same in both groups. All the patients were evaluated for toxicity and survival according to the as-treated principle. Results: With a median follow-up of 26.3 months (range 3-74.6 months), 59% of patients in the cisplatin arm completed the planned concurrent chemoradiation treatment, compared to 73% in the carboplatin arm. Forty-two percent of cisplatin patients completed the 3 cycles of adjuvant therapy compared to 70% in the carboplatin group. There were more renal toxicity, leucopenia, and anaemia in the cisplatin group, and more thrombocytopenia in the carboplatin arm. The 3 year disease free survival rates were 63.4% for the cisplatin group and 60.9% for the carboplatin group (p = 0.9613) (HR 0.70, 95% confidence interval (CI): 0.50-0.98). The 3 year overall survival rates were 77.7% and 79.2% for cisplatin and carboplatin groups, respectively (p = 0.9884) (HR 0.83, 95% CI: 0.63-1.010). Conclusion: We concluded that the tolerability of carboplatin based regimen is better than that of the cisplatin regimen. Moreover, the treatment efficacy of carboplatin arm is not different from the standard regimen in the treatment of locoregional advanced stage NPC. © 2007 Elsevier Ltd. All rights reserved.